(untitled) (Research, Society and Development, 2019)
The objective of this study was to evaluate blood pressure, anthropometric levels and the vaccination status of workers in the health unit. It is an intervention project that was carried out in the Pantanal Family Health Strategy. This project was developed through the survey carried out with the UBS team on the primary health care needs of the health of the man and the worker of the neighborhood industries. For the development of this work the methodology of Charles Maguerez was used. In the first company, 13 men participated in the intervention. As for the vaccine situation, none of them had vaccination card and reported not remembering the last time they received any dose of any vaccine. In the second, 14 men participated in the activities. As for the vaccination situation, they were the same as the first company and the same measures and procedures were adopted. The activities carried out with the workers of the neighborhood factories made it possible to bring the workers closer to the health services, making it possible to provide services to the male population in their specificities, and covering the principles of integrality, equity and universality of health actions, services provided in the unit and ensuring workers’ rights.